Digital-Based Learning: Strategy, Design, and Management at Universitas Muhammadiyah Metro - Wahyu Febriana; Agus Pahrudin; Yuberti Yuberti; Achi Rinaldi (CV. Bimbingan Belajar Assyfa, 2026)
Digital-Based Learning (DBL) has become a necessity in higher education transformation during the fourth industrial revolution era. This study aims to analyze the strategies, design, and management of the DBL program at Universitas Muhammadiyah (UM) Metro as an effort to improve learning quality. Using a qualitative approach with a case study method, this research involved 25 informants consisting of university leaders, lecturers, educational staff, and students. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that DBL implementation at UM Metro encompasses three main components: (1) DBL strategies integrating blended learning, flipped classroom, and AI-based Learning Management System (LMS) utilization; (2) DBL design applying Universal Design for Learning (UDL) principles and developing interactive digital teaching materials; and (3) DBL management through data-based planning, lecturer competency development, and continuous evaluation. The research findings reveal that DBL success is determined by the synergy between institutional policies, infrastructure readiness, and human resource capacity. This study contributes to the development of DBL implementation models in higher education and provides practical recommendations for stakeholders in optimizing educational digital transformation